TRAFFIC BREAKDOWN MECHANISM OF HIDDEN BOTTLENECK: A CASE STUDY OF U-TURN SECTION ON AN ARTERIAL ROAD - Sugiarto Sugiarto (JURNAL TEKNIK SIPIL, 2012)
Abstract: The Traffic breakdown mechanisms were studied on arterial road of T. Nyak Arief Road specifically at in front of Zainal Abidin General Hospital which is median opening exist. Studies were conducted during three days a week including morning and evening peak hours. The diagnostic tools used in this work were oblique cumulativ plots and breakdown event fuction methods. Both methods are time series treatment between cumulative vehicles arrival versus time contracted from data recorded by video tape. It is clearly shown that in certain time during an hour observation bottleneck becomes active then breakdown occurs on average 39 minutes within an hour on u-turn section. Finding from this work on average capacity drops in median opening approximately in the range 8-9 percent controlled by capacity in immediately before breakdown. Performing by breakdown event method, speed founded drop on average 10 percent effected by median opening.Keywords : Breakdown mechanism, Oblique Cumulative Plots, Breakdown Event Fuction, U-Turn, speed and capacity drops.Abstrak: Studi mekanisasi hambatan lalu lintas dilakukan pada jalan arteri perkotaan Jalan T. Nyak Arief tepatnya di depan RSU. Zainal Abidin dimana merupakan lokasi bukaan median. Penelitian dilakukan selama 3 (tiga) hari dalam seminggu termasuk pada jam puncak pagi dan sore. Oblique cumulative plots dan breakdown event function methods digunakan sebagai alat pendiagnosa mekanisasi aliran lalu lintas di lokasi penelitian. Kedua metode ini adalah kurva hubungan antara jumlah kumulatif kedatangan kendaraan terhadap waktu kedatangan yang dibangun dari hasil ekstrak data yang terekam dengan alat video kamera. Hasil memperlihatkan bahwa selama pengamatan jam puncak hambatan puncak (kemacetan) terjadi rata-rata selama 39 menit selama 1 (jam) pengamatan yang diakibatkan oleh keberadaan bukaan median. Penurunan kapasitas yang terjadi pada aliran utama akibat bukaan median berkisar 8-9 persen dikontrol dari kondisi sebelum terjadinya gangguan yang berarti (kemacetan). Ditinjau dari penurunan kecepatan pada aliran utama akibat bukaan median rata-rata 10 persen.Kata kunci : Mekanisasi kemacetan, Oblique Cumulative Plots, Breakdown Probability, Bukaan  median, penurunan kecepatan dan kapasitas.